Learning Islamic Education in the Era of the Industrial Revolution 4.0 and Society 5.0: A Study on the Wahdah Islamiyah Organization - Fadillah, Ana Tasya Nur; Istanto, Istanto (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The purpose of this research is to comprehensively examine the implementation of Islamic education learning and the development of Islamic values carried out by Wahdah Islamiyah Bejen. This study uses a descriptive qualitative approach with a case study method to answer the challenges of the industrial era 4.0 and society 5.0. Data was collected through online interviews with the management of Wahdah Islamiyah Bejen, Karanganyar and a literature review of books and relevant scientific journal articles. This method was chosen to expand the understanding of the approach, implementation, and process of Islamic learning that occurs in Wahdah Islamiyah mass organizations. The results of the study show that Wahdah Islamiyah Bejen, Karanganyar develops Islamic education that is adaptive and responsive to technological advances with programs such as learning the Qur'an, Tahsin Al-Qur'an, Tahfidz Al-Qur'an, and Tarbiah Islamiyah. These programs are implemented in stages, systematically, and supported by digital media. Strengthening Islamic digital literacy, implementing human-centered hybrid learning, technology-adaptive education management, and Islamic digital content development.